2011
DOI: 10.1186/1471-2180-11-84
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analyses place most Spanish isolates of Beauveria bassiana in a molecular group with word-wide distribution

Abstract: BackgroundThe entomopathogenic anamorphic fungus Beauveria bassiana is currently used as a biocontrol agent (BCA) of insects. Fifty-seven Beauveria bassiana isolates -53 from Spain- were characterized, integrating group I intron insertion patterns at the 3'-end of the nuclear large subunit ribosomal gene (LSU rDNA) and elongation factor 1-alpha (EF1-α) phylogenetic information, in order to assess the genetic structure and diversity of this Spanish collection of B. bassiana.ResultsGroup I intron genotype analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 35 publications
2
10
0
3
Order By: Relevance
“…However, they have also shown that these approaches are insufficient to investigate species such as B. bassiana (Rehner and Buckley, 2005). Phylogenetic analysis of the sequences of EF1-a resulted in cladograms with higher resolution, consistent with the results of Rehner and Buckley (2005) and Garrido-Jurado et al (2011). The resulting topologies of phylogenetic analyses of sequences of the ITS and EF1-α genes separately, were highly similar to the topologies obtained by Rehner and Buckley (2005).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, they have also shown that these approaches are insufficient to investigate species such as B. bassiana (Rehner and Buckley, 2005). Phylogenetic analysis of the sequences of EF1-a resulted in cladograms with higher resolution, consistent with the results of Rehner and Buckley (2005) and Garrido-Jurado et al (2011). The resulting topologies of phylogenetic analyses of sequences of the ITS and EF1-α genes separately, were highly similar to the topologies obtained by Rehner and Buckley (2005).…”
Section: Discussionsupporting
confidence: 82%
“…Species recognition in Beauveria is difficult due to a lack of taxonomically informative morphology. A molecular phylogenetic analysis, based on nuclear ribosomal internal transcribed spacer (ITS) and elongation factor 1-alpha (EF1-α) sequences for isolates from diverse geographic origins, habitats and insect hosts, was used to resolve six well supported clades within Beauveria bassiana Vuillemin (Rehner and Buckley, 2005; Garrido-Jurado et al ., 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Studies on the genetic diversity of entomopathogenic Hypocreales have typically been performed using isolates from culture collections (Garrido-Jurado et al, 2011), by infecting a certain pest (Aquino de Muro et al, 2005;Rehner et al, 2006), by focusing on one habitat (Hollingsworth et al, 2011;Schneider et al, 2012;Inglis et al, 2008;Meyling and Eilenberg, 2006a,b), or by collecting specimens from regions worldwide (Freed et al, 2011). None of these studies has simultaneously increased the understanding of species ecology on a local scale and in habitats in different ecosystems (Meyling and Eilenberg, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…El gen nuclear EF-1α fue amplificado, secuenciado y analizado en las diferentes muestras. Un fragmento de 1100 pares de bases de dicho gen se amplificó con los primers tef1fw (O'Donnell et al, 1998) y 1750-R (Garrido-Jurado et al, 2011. Las alineaciones se generaron utilizando el programa MegAlign (DNASTAR, 1989-92, Londres, Reino Unido).…”
Section: Aislamiento Y Caracterización De Los Hongosunclassified